Assessing health science students’ English language lacks: learners’ needs analysis - Gayessa, Tessema Gilo; Mohammed, Nuru (ELT Forum: Journal of English Language Teaching, 2024)
English language courses are provided in universities throughout the majority of the world where English is used as a second or first language to address students' English language needs in the target-situation use. However, at all Ethiopian Universities where English is taught as a foreign language, two English language skills courses, dubbed "communicative English language skills I" and "communicative English language skills II," are offered as standard courses in the first year. Large language gaps have been noted, particularly in health science academic and professional settings where English is largely expected. Hence, this study aimed to identify Health Science students’ English language gaps so that English language courses are designed accordingly. This study employed a mixed-methods research design. It was conducted via tests, observations, and interviews. The findings revealed that participant students had good proficiency in grammar and usage as well as reading skills. However, they had poor proficiency in listening skills, which in turn indicated that the students had difficulty understanding spoken English. The findings also indicated that these students demonstrated an inability to write an acceptable essay. The study further revealed that students' failure to describe a patient, the case, the complaints, and the drugs in medical terminology was partially due to a lack of English language skills. As a result, while developing English language course materials for health science students, course designers and practitioners should address these English language gaps existing in students’ academic studies and future professions.